Exogenous sodium nitroprusside alleviates arsenic-induced oxidative stress in wheat (Triticum aestivum L.) seedlings by enhancing antioxidant defense and glyoxalase system - Hasanuzzaman, Mirza; Fujita, Masayuki (Ecotoxicology (London), 2013)
The present study investigates the possible regulatory role of exogenous nitric oxide (NO) in mitigating oxidative stress in wheat seedlings exposed to arsenic (As). Seedlings were treated with NO donor (0.25 mM sodium nitroprusside, SNP) and As (0.25 and 0.5 mM Na 2 HAsO 4 ·7H 2 O) separately and/or in combination and grown for 72 h. Relative water content (RWC) and chlorophyll (chl) content were decreased by As treatment but proline (Pro) content was increased. The ascorbate (AsA) content was decreased significantly with increased As concentration. The imposition of As caused marked increase in the MDA and H 2 O 2 content. The amount of reduced glutathione (GSH) and glutathione disulfide (GSSG) significantly increased with an increase in the level of As (both 0.25 and 0.5 mM), while the GSH/GSSG ratio decreased at higher concentration (0.5 mM). The ascorbate peroxidase and glutathione S -transferase activities consistently increased with an increase in the As concentration, while glutathione reductase (GR) activities increased only at 0.25 mM. The monodehydroascorbate reductase (MDHAR) and catalase (CAT) activities were not changed upon exposure to As. The activities of dehydroascorbate reductase (DHAR) and glyoxalase I (Gly I) decreased at any levels of As, while glutathione peroxidase (GPX) and glyoxalase II (Gly II) activities decreased only upon 0.5 mM As. Exogenous NO alone had little influence on the non-enzymatic and enzymatic components compared to the control seedlings. These inhibitory effects of As were markedly recovered by supplementation with SNP; that is, the treatment with SNP increased the RWC, chl and Pro contents; AsA and GSH contents and the GSH/GSSG ratio as well as the activities of MDHAR, DHAR, GR, GPX, CAT, Gly I and Gly II in the seedlings subjected to As stress. These results suggest that the exogenous application of NO rendered the plants more tolerant to As-induced oxidative damage by enhancing their antioxidant defense and glyoxalase system.